Tibetan Medicines and Tibetan Prescriptions for the Treatment of Diabetes Mellitus - Gao, Jie (Evid Based Complement Alternat Med, 2021)
Diabetes mellitus (DM) is one of the most serious diseases threatening human health and because of that, it is imperative to look for drugs to tackle it. The Tibetan medicine, a traditional medical system used in China, is currently being the focus of research towards the discovery of new effective drugs against several diseases. Based on the literature survey of Tibetan medicine monographs and drug standards, the Tibetan medicine, and Tibetan prescription used in the traditional Tibetan medical system, here, we summarise the methods indicated for DM treatment. In the Tibetan medical system, 56 types of Tibetan medicine and 25 Tibetan prescriptions were found for the treatment of DM. The most commonly used are Curcuma, Berberidis Cortex, and Carthami Flos. Their names, families, medicinal parts, phytochemical components, and pharmacological activities were described in detail in our research. These Tibetan medicines and prescriptions are valuable gifts from the Tibetan medicine to the world and may be the source of potential drugs for the treatment of DM. With the help of modern phytochemistry, pharmacology, metabonomics, and/or clinical trial methods, further research is needed to prove its medicinal value, identify bioactive components, elucidate potential mechanisms of action, and assess potential side effects or toxicity. This study provides the first available data compilation for the ethnic medical knowledge of Tibetan medicine for the treatment of DM, providing new ideas and sources for drugs against DM.